Accounting approaches to the study of historical Tamil events - Chinnasamy, Thangavelu (De Computis, Revista Española de Historia de la Contabilidad., 2026)
This study examines the historical development of accounting in Tamil civilization based on archaeological, literary, epigraphic, and administrative evidence, tracing its evolution from the Sangam period (300 BCE–300 CE) to the institutional systems of the Chola and Pandya dynasties (9th–14th centuries CE). Findings from sites such as Keeladi, Adichanallur, and Poompuhar reveal early urban and commercial organization that required structured economic record-keeping. Tamil literary sources, including the Thirukkural and Sangam anthologies, along with temple inscriptions and palm-leaf manuscripts, document taxation systems, land administration, treasury control, and auditing practices. Merchant guilds and international trade networks further demonstrate a highly organized economy connected with the Greco-Roman and Arab worlds, as evidenced in the Periplus of the Erythraean Sea. In the contemporary context, the study highlights the continuity of indigenous accounting traditions alongside the adoption of digital systems, emphasizing the importance of interdisciplinary approaches to understanding the evolution of Tamil accounting within a broader global economic history.